Characterization of Boride Coatings on AISI 8620 Steels without and with Hydrogen Permeation - Marco Antonio Doñu Ruiz; Ernesto David García Bustos; Tomas de la Mora Ramirez; David Sánchez Huitron; Víctor Jorge Cortes Suarez; Noé López Perrusquia (Advances in Materials Science and Engineering)
The present work studied the characterization of boriding coatings without and with exposed hydrogen permeation on AISI 8620 through microstructure and mechanical behavior. A dehydrated paste pack process was carried out for the formation of boride coatings on AISI 8620 at 1173, 1223, and 1273 K for 6 h of exposure time for each temperature. After boronizing, hydrogen was introduced into the borided steels by in situ cathodic charging using an H2SO4 acid electrolyte. Specimens borided without and with hydrogen were characterized by scanning electron microscopy with energy dispersive spectroscopy and X-ray diffraction. The experimental techniques of the Vickers microhardness and three-point bending were used. As a result, the hydrogen diffusion on steel AISI 8620 borided shows a significant increase in microhardness. Furthermore, three-point bend tests showed an increased strength on 8620 steel borided. However, the ductility and strength value on 8620 steel borided surfaces presented a drastic reduction due to hydrogen permeation. The results revealed that the borided coatings provided strength and reduced the hydrogen embrittlement index on AISI 8620 borided.